equação do 1 grau (35 pontos)
a) -3.(3x-42)=2.(7x-52)
b) ![\frac{2(x-1)}{3} + \frac{3(1+x)}{2} = \frac{1}{2} - \frac{x-1}{3} \frac{2(x-1)}{3} + \frac{3(1+x)}{2} = \frac{1}{2} - \frac{x-1}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%28x-1%29%7D%7B3%7D+%2B+%5Cfrac%7B3%281%2Bx%29%7D%7B2%7D+%3D+%5Cfrac%7B1%7D%7B2%7D+-+%5Cfrac%7Bx-1%7D%7B3%7D+)
c) ![\frac{3x-1}{2}- \frac{4x+2}{4} - \frac{2x-4}{3} = \frac{x-5}{6} \frac{3x-1}{2}- \frac{4x+2}{4} - \frac{2x-4}{3} = \frac{x-5}{6}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x-1%7D%7B2%7D-+%5Cfrac%7B4x%2B2%7D%7B4%7D+-++%5Cfrac%7B2x-4%7D%7B3%7D+%3D++%5Cfrac%7Bx-5%7D%7B6%7D+)
d) ![\frac{3x+1}{2} - (1-x)= \frac{x-1}{4} \frac{3x+1}{2} - (1-x)= \frac{x-1}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B3x%2B1%7D%7B2%7D+-+%281-x%29%3D++%5Cfrac%7Bx-1%7D%7B4%7D+)
Soluções para a tarefa
Respondido por
2
a) -3.(3 x - 42) = 2 (7 x - 52) =
-9 x + 126 = 14 x - 104 =
-9 x -14 x = -104 - 126 =
-23 x = -230
x = -230/-23
x = 10
b)2 (x - 1 ) 3(1 + x ) 1 x - 1
----------- + ------------- = ---- - ---------
3 2 2 3
m.m.c = 6
4(x - 1 ) + 9(1 + x) = 3 - 2(x - 1)
4 x - 4 + 9 + 9 x = 3 - 2 x + 2
13 x + 5 = -2 x + 5
13 x + 2 x = -5 + 5
15 x = 0
x = 0/15
x = 0
c)3 x - 1 4 x + 2 2 x - 4 x - 5
-------- - ---------- - ---------- = --------
2 4 3 6
m.m.c = 12
6(3 x - 1 ) - 3 (4x + 2) - 4(2 x - 4 ) = 2( x - 5 )
18 x - 6 - 12 x - 6 - 8 x + 16 = 2 x - 10
18 x - 12 x - 8 x - 6 - 6 + 16 = 2 x - 10
18 x - 20 x - 12 + 16 = 2 x - 10
- 2 x + 4 = 2 x - 10
-2 x - 2 x = -10 - 4
- 4 x = - 14
x = -14/-4 simplificando por 2
x = 7/2
d)3 x + 1 (1 - x ) x - 1
----------- - -------- = ---------
2 1 4
m.m.c = 4
6x + 2 - 4 + 4 x = x - 1
10 x - 2 = x - 1
10 x - x = - 1 + 2
9 x = 1
x = 1/9
-9 x + 126 = 14 x - 104 =
-9 x -14 x = -104 - 126 =
-23 x = -230
x = -230/-23
x = 10
b)2 (x - 1 ) 3(1 + x ) 1 x - 1
----------- + ------------- = ---- - ---------
3 2 2 3
m.m.c = 6
4(x - 1 ) + 9(1 + x) = 3 - 2(x - 1)
4 x - 4 + 9 + 9 x = 3 - 2 x + 2
13 x + 5 = -2 x + 5
13 x + 2 x = -5 + 5
15 x = 0
x = 0/15
x = 0
c)3 x - 1 4 x + 2 2 x - 4 x - 5
-------- - ---------- - ---------- = --------
2 4 3 6
m.m.c = 12
6(3 x - 1 ) - 3 (4x + 2) - 4(2 x - 4 ) = 2( x - 5 )
18 x - 6 - 12 x - 6 - 8 x + 16 = 2 x - 10
18 x - 12 x - 8 x - 6 - 6 + 16 = 2 x - 10
18 x - 20 x - 12 + 16 = 2 x - 10
- 2 x + 4 = 2 x - 10
-2 x - 2 x = -10 - 4
- 4 x = - 14
x = -14/-4 simplificando por 2
x = 7/2
d)3 x + 1 (1 - x ) x - 1
----------- - -------- = ---------
2 1 4
m.m.c = 4
6x + 2 - 4 + 4 x = x - 1
10 x - 2 = x - 1
10 x - x = - 1 + 2
9 x = 1
x = 1/9
Perguntas interessantes